What motivates urban dwellers to adapt to climate-driven water insecurity? An empirical study from Lima, Peru. Issue 136 (October 2022) - Flórez Bossio, Camila; Coomes, Oliver T.; Ford, James
Abstract: This paper reports on a study of the determinants of adaptive behavior in face of climate-driven water insecurity, using a survey of 400 urban dwellers in Lima, Peru. Lima is characterized by continuous water stress and is at risk of permanent water scarcity due to climate change. Residents show a general understanding that the climate is changing and have recent experience with climate extremes. We use regression analyses to identify the socioeconomic, socio-institutional, and psychological determinants of adaptive behavior. We examine the differences between climate-responsive and general adaptive behavior, using five indices – structural, knowledge, consumption, planning, and environmental – to identify and compare the determinants of both behaviors. Our findings show that education, extended water availability, climate change concern, and cultural environmental values influence adaptive behavior, and each thematic index has distinct set of significant behavioral determinants. We discuss the importance of water-related determinants, the intentionality of adaption behavior, and the need to contextualize the social and psychological realities of urban dwellers in the Global South. Highlights: Education, extended water availability, climate change concern, and cultural environmental values influence adaptive behavior. The climate-responsive and general adaptive behavior determinants that differ are related to self-transcendence values. Water-specific urban processes prove significant to explain adaptive behavior. Individuals' social distance to climate change does not prevent them from adapting to climate change. The assumption that social trust is a condition for adaptation is contested.